SADAR WISATA, KEMENARIKAN FASILITAS, JARAK, PENGARUHNYA TERHADAP MINAT BERKUNJUNG KEMBALI PADA OBJEK WISATA MASJID AGUNG JAWA TENGAH DI KOTA SEMARANG - Rina Fitriani; Setia Budhi Wilardjo (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
Attraction Masjid Agung Jawa Tengah has great potential, especially in religious tourism and historical value. Masjid Agung Jawa Tengah have the advantage in a strategic location in Semarang, Central Java. Attraction Masjid Agung Jawa Tengah stand firmly whitin building with unique arsitectur and other unique. Methods used in collecting primary data by using convenient random sampling. Dependent variable is interest come back to attaction Masjid Agung Jawa Tengah, and the three independent variable are Tourism Awareness (X1), Attraction Facilities (X2), and Distance (X3). The testing of the hypothesis identified the following: not a positive and significant influence between the Tourism Awareness from the point of interest come back to Masjid Agung Jawa Tengah. A positive and significant influence between Attraction Facilities and Distance from the point of interest come back to Masjid Agung jawa Tengah. From the three variables that influence the interest come back to Masjid Agung Jawa Tengah the most important was the Attraction Facilities. From the results of the regression analysis using SPSS 16.0 program obtained at 0.468 R2 where the independent variables can be explained by 46.8% and the remaining 53.2% is explained by variables outside the research model. By using a 0.05 significance level obtained F-table value of 2.70, then the F-count (28.192)> from the F-table (2.70) it can be concluded that the three independent variables affect have an effect on the interest of visit attractions Masjid Agung Jawa Tengah